The Criminalization of Polygamy in Indonesia’s New Penal Code: Perspectives of Legal Certainty and Gender Justice - M. Johan Pakpahan; Rineke Sara (CV. Green Publisher Indonesia, 2026)
This study examines the criminalization of polygamy under Indonesia’s new Penal Code, with particular emphasis on legal certainty and gender justice. The study is grounded in the normative tension between criminal law and marriage law in Indonesia, where polygamy remains conditionally permissible under marriage law but may give rise to criminal liability when legal requirements are violated. This research employed a normative legal method using statutory, conceptual, and case approaches. The legal materials consist of legislation, court decisions, and relevant legal scholarship. The findings indicate that the criminalization of polygamy under the new Penal Code still leaves room for legal uncertainty, particularly regarding the distinction between lawful polygamy and punishable conduct. Moreover, from the perspective of gender justice, the current legal framework has not yet provided optimal protection for women and children as vulnerable parties. Therefore, a comprehensive reconstruction of criminal law policy is required in order to establish a more coherent and human rights-oriented legal framework. Such reform is essential to achieving legal certainty and gender justice in the regulation and practice of polygamy in Indonesia.